Knowledge and Prevalence of Dental Trauma among Amateur Soccer Players in a Brazilian Subpopulation: A Cross-Sectional Study - Felipe de Souza Matos; André de Lima Ferreira; Ana Beatriz Bomfim Gomes Ribeiro; Vinicius Grangeiro Leite Bezerra; Douglas Teixeira da Silva; Millena Barroso Oliveira; Luiz Renato Paranhos (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To investigate the knowledge and prevalence of dental trauma among amateur soccer players in a Brazilian subpopulation. Material and Methods: The players responded to a 20-item questionnaire on personal characteristics and the prevalence, education, and management of dental injuries between June and August 2023. Five questions with a five-point scoring system evaluated participant knowledge about managing coronal fractures and avulsion. The Mann-Whitney U-test and the Kruskal-Wallis test (p<0.05) compared the subcategories of personal characteristics and education on dental trauma management. Results: Two hundred forty-four (244) amateur soccer players participated in the study, with 55 (22.55%) reporting experiences of traumatic dental injury during games and a higher frequency of coronal fractures. The median score for correctly managing coronal fractures and avulsion was 2.0 points. Athletes with health education/occupation showed a higher median value (3.0 points). Only 9.43% of participants use or have used a mouthguard during sports practice. The study identified a 22.55% prevalence of dental trauma among amateur soccer players. Conclusion: The knowledge of athletes about managing coronal fractures and avulsion is insufficient and requires improvement.